Investigation of failure in Kevlar fabric under transverse indentation using a homogenized continuum constitutive model. Issue 4 (March 2014) - Manimala, James M; Sun, CT
Kevlar fabrics are extensively used in ballistic protection and containment applications. This study presents an investigation of failure for Kevlar fabrics under their in-service deformation mode of transverse indentation using a homogenized continuum constitutive model. Quasi-static indentation tests performed on uniaxial and 45° off-axial Kevlar K706 coupons with and without an elastic foundation were used to investigate failure modes and mechanisms. Two failure modes were identified – yarn breakage and yarn sliding, depending on the configurations of the tests. A stress-based failure criterion in conjunction with the constitutive model was implemented in numerical simulations to predict load–displacement behavior and failure load with good accuracy for the uniaxial case where the failure was due to yarn breakage. For the 45° off-axial case, an estimation of onset of failure due to yarn sliding is achieved based on a yarn locking parameter. The deformed shape and load–displacement behavior for the combined indentation tests with the elastic foundation are accurately captured by the model. This approach provides a relatively simple, computationally efficient means to predict failure due to yarn-scale phenomenon using homogenized properties for the fabric.